Effect of verapamil in the treatment of type 2 long QT syndrome is not a dose-dependent pattern: a study from bedside to bench, and back. (1st March 2016) - Liu, Yang; Xue, Yumei; Wu, Shulin; Duan, Jialin; Lin, Li; Wang, Lin; Zhang, Cuntai; Liu, Nian; Bai, Rong
Abstract: Type 2 long QT syndrome (LQT2) is caused by loss-of-function mutations in KCNH2 gene. This study aimed to investigate the efficacy and mechanism of a calcium channel blocker, verapamil, to improve clinical manifestations in LQT2. A 42-year-old woman with a LQT2 phenotype underwent candidate gene screening. Therapeutic effects of verapamil were evaluated by QT-interval measurement and shock count of implantable cardioverter-defibrillator. The electrophysiological effect of verapamil was assessed in a LQT2 model using rabbit ventricular wedge preparations. Direct sequencing of her DNA revealed a heterozygous D609N mutation in KCNH2 . Acute administration of intravenous verapamil (10 mg/h) successfully abolished electrical storm and shortened the corrected QT (QTc) from 671 to 532 ms in the patient. However, long-term use of oral verapamil (240 mg daily) failed to completely prevent the torsades de pointes (TdP) recurrence over a 3-year follow-up period, whereas a low dose of oral verapamil (120 mg daily) totally suppressed the cardiac events in the following 12 months. In in vitro studies, verapamil preferentially abbreviated endocardial action potential duration leading to a reduction in the QT interval and transmural dispersion of repolarization, and suppressed early afterdepolarization. However, high concentration of verapamil caused a signiﬁcant decrease in both myocardial effective refractory period (ERP) and post-repolarization refractoriness (PRR), which facilitated TdP in the LQT2 model. Our findings indicate a therapeutic role of verapamil in the management of LQT2 patients. However, an inappropriate dose of verapamil may offset beneficial effects by excessively shortening the ERP and PRR to increase the myocardial excitability.